Coalgebraic Methods in Computer Science 11th International Workshop, CMCS 2012, Colocated with ETAPS 2012, Tallinn, Estonia, March 31 -- April 1, 2012, Revised Selected Papers - Pattinson, Dirk; Schröder, Lutz (Theoretical Computer Science and General Issues, 2012)
This book constitutes the thoroughly refereed post-proceedings of the 11th International Workshop on Coalgebraic Methods in Computer Science, CMCS 2012, colocated with ETAPS 2012, held in Tallin, Estonia, in March/April 2012. The 10 revised full papers were carefully reviewed and selected from 23 submissions. Also included are three invited talks. The papers cover a wide range of topics in the theory, logics and applications of coalgebras.